PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA DASAR I MODEL PEMBELAJARAN PROJECT BASED LEARNING DI PRODI PENDIDIKAN FISIKA UNIVERSITAS PASIR PENGARAIAN - Asra, Azmi; -, Ratnawulan; -, Yulkifli (Edu Research, 2015)
Classroom situations that are less motivated, there is no teaching materials that can guide students' self-learning and learning-centered to lecturers resulted in students having difficulty in understanding the matter and solve the problems. This situation would require settlement solutions, including need to develop learning material that can help improve learning outcomes and student motivation and stimulate students to be more active. Among them learning material in the form of modules and learning model that can involve the activity of students, learning independently and carry out a project and collaborate to improve learning outcomes and produce a product that can be communicated to others. This type of research was research and development. The development model used is the 4-D comprising the steps of defining, design, development and disseminates. Subjects were students of class I A and B Physics Education Major Faculty of Education and Teacher Training Pasir Pengaraian University. Data were collected using the data collection instruments. Based on development and dissemination test, it has been found that the learning material in Basic Physics I using a project-based learning model could address the needs of students in the Physical Education in learning activities.